Correlation of quantitative parameters of magnetic resonance perfusion‐weighted imaging with vascular endothelial growth factor, microvessel density and hypoxia‐inducible factor‐1α in nasopharyngeal carcinoma: Evaluation on radiosensitivity study. (10th October 2017) - Hu, Y.; E, H.; Yu, X.; Li, F.; Zeng, L.; Lu, Q.; Xi, X.; Shen, L.
Abstract : Objectives: To investigate the correlation of parameters of magnetic resonance perfusion‐weighted imaging (MR‐PWI) with the expression of vascular endothelial growth factor (VEGF), hypoxia‐inducible factor‐1α (HIF‐1α) and microvessel density (MVD) in nasopharyngeal carcinoma (NPC) so as to explore the value of predicting radiosensitivity. Design: A prospective study. Setting: Department of Head‐and‐neck radiotherapy in Hunan Cancer Hospital. Participants: Ninety‐four patients of NPC were included between December 2013 and December 2014. Main outcome measures: The expression of VEGF, MVD and HIF‐1α was studied by immunohistochemistry, and magnetic resonance perfusion‐weighted imaging (MR‐PWI) was performed before and after undergoing radiotherapy (20 Gy dose). Parameters of MR‐PWI, volume of primary tumour and rate of tumour remission were measured and calculated. Patients with primary local tumour were then divided into completely response group (CR group) and partially response group (non‐CR group) according to tumour regression condition. Relevant parameters were analysed by Spearman, and diagnostic efficiency of radiosensitivity was analysed by receiver operating characteristic curve (ROC). Results: The expression of VEGF was positively correlated with MVD ( r  = .322, P  < .05), but the expression of HIF‐1α was no significant correlations with VEGF and MVD. The expression VEGF was in positive correlation with fractional plasma volume (fpv) ( r  = .339, P  = .05) before radiotherapy. There was a significant difference in the quantitative parameters of MR‐PWI between CR group and non‐CR group during the course of radiotherapy and at the end of radiotherapy treatment. The change of blood reflux constant (Δkep20) and extravascular extracellular space volume fraction (ΔVe20) before and after treatment was positively correlated with primary local tumour remission condition after 3 month treatment; Δkep and ΔVe were negatively correlated with primary local tumour remission condition after 3 months. Tumour regression rate was only positively correlated with Ve and the average volume of primary tumour after 2 week treatment (V1). ROC curve showed that R20 ≥ 65.69%, and was considered as a threshold to predict primary local tumour remission, with a sensitivity of 0.84 and specificity of 0.69, and area under the curve was 0.819 ( P  = .000). Conclusions: The parameters of MR‐PWI with the expression of VEGF, HIF‐1α and MVD could be guidance for predicting radiosensitivity in NPC.